2019
DOI: 10.1007/s00167-019-05481-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased rates of knee arthroplasty and cost of patients with meniscal tears treated with arthroscopic partial meniscectomy versus non-operative management

Abstract: Purpose The purpose of this study was to determine the cost of arthroscopic partial meniscectomy (APM), one of the most common surgeries performed by orthopaedic surgeons, and the associated rate of progression to knee arthroplasty (KA) compared to patients treated non‐operatively after diagnosis of meniscal tear. Methods Utilizing data mining software (PearlDiver, Colorado Springs, CO), a national insurance database of approximately 23.5 million orthopaedic patients was queried for patients diagnosed with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 38 publications
(61 reference statements)
0
28
0
1
Order By: Relevance
“…The increased rate of knee arthroplasty after meniscectomy further confirms the results of previous studies, with up to 51.5% of patients requiring knee arthroplasty after meniscectomy compared with 33.5% after meniscal repair at the 10-year follow-up. 1,5,13,29 Abram et al 1 utilized the National Health Service database of England to determine that 0.67% of patients who underwent meniscectomy between the ages of 20 and 39 years required subsequent knee arthroplasty. This is similar to the current study, with 1.5% requiring total knee arthroplasty in similar aged patients with similar follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased rate of knee arthroplasty after meniscectomy further confirms the results of previous studies, with up to 51.5% of patients requiring knee arthroplasty after meniscectomy compared with 33.5% after meniscal repair at the 10-year follow-up. 1,5,13,29 Abram et al 1 utilized the National Health Service database of England to determine that 0.67% of patients who underwent meniscectomy between the ages of 20 and 39 years required subsequent knee arthroplasty. This is similar to the current study, with 1.5% requiring total knee arthroplasty in similar aged patients with similar follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to a relatively low incidence of knee arthroplasty compared with older patients undergoing meniscectomy or meniscal repair in other studies. 1,5,13,29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 35 Approximately 10% of patients undergoing meniscectomy require a TKA within 1 year of the initial meniscectomy. 36 , 37 Barnds et al. demonstrated that arthroscopic partial meniscectomy survived 9 months before patients received TKA.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that arthroscopic partial meniscectomy survived 9 months before patients received TKA. 36 In younger, more active patients with persistent symptoms following meniscectomy, surgeons may offer patients revision arthroscopy or other interventions, such as meniscal scaffolds, meniscal allograft transplantation or, in the case of advanced osteoarthritis, off-loading osteotomies or joint replacement. 38 Surgeons may be reluctant to offer TKA to younger patients because they face the risk of revision TKA at a younger age as well as the potential for multiple revision arthroplasties.…”
Section: Discussionmentioning
confidence: 99%